Effectiveness of a fish ladder for two Neotropical migratory species in the Paraná River - Gutfreund, Carola; Makrakis, Sergio; Castro-Santos, Theodore; Celestino, Leandro Fernandes; Dias, João Henrique Pinheiro [UNESP]; Makrakis, Maristela Cavicchioli (CSIRO Publishing, 2018)
We evaluated the effectiveness of the fish ladder at Porto Primavera Dam in the severely regulated Upper Paraná River, for two Neotropical migratory fish species. Overall, 564 fish (448 Megaleporinus obtusidens and 116 M. piavussu) were PIT-tagged, released in upstream and downstream areas (on the left and right banks), and monitored continuously for 4 years. The fish performed two-way movements through the fish ladder, ascending from the tailrace and descending from the forebay. We registered entry into the fishway of 46 M. obtusidens (10.3%) individuals and only three M. piavussu (2.6%) individuals; therefore, all analyses were focussed on M. obstusidens. Entry proportion ranged from 0 to 48.1%, depending on the release site, and was greatest for fish released downstream near the fishway entrance. Entry times ranged from 3.0 to 384.0 days, and median times were 32.9 and 25.8 days for downstream and upstream respectively. Of fish that entered the fishway, passage percentages were 80% for fish released downstream and 100% for fish released upstream, and median transit times were 0.7 and 0.9 h respectively. Results suggest that if guidance and entry conditions can be improved, this fishway design holds promise as an effective solution for providing passage in both directions.
Keywords: attraction; efficiency; fishway; migration; PIT-tag